2014
DOI: 10.1038/srep05281
|View full text |Cite
|
Sign up to set email alerts
|

Tug-of-war of microtubule filaments at the boundary of a kinesin- and dynein-patterned surface

Abstract: Intracellular cargo is transported by multiple motor proteins. Because of the force balance of motors with mixed polarities, cargo moves bidirectionally to achieve biological functions. Here, we propose a microtubule gliding assay for a tug-of-war study of kinesin and dynein. A boundary of the two motor groups is created by photolithographically patterning gold to selectively attach kinesin to the glass and dynein to the gold surface using a self-assembled monolayer. The relationship between the ratio of two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
(108 reference statements)
1
10
1
Order By: Relevance
“…In [61], it was shown that silicon nanowires covered with myosin can be used as tracks for actin filaments. Dynein molecular motor and microtubule filaments is another example of motor protein-filament motility [62]. It is also possible to use active transport in conjunction with flow based propagation in microfluidic lab-on-chip devices as was shown in [63].…”
Section: ) Microtubule Filament Motility Over Stationary Kinesinmentioning
confidence: 99%
“…In [61], it was shown that silicon nanowires covered with myosin can be used as tracks for actin filaments. Dynein molecular motor and microtubule filaments is another example of motor protein-filament motility [62]. It is also possible to use active transport in conjunction with flow based propagation in microfluidic lab-on-chip devices as was shown in [63].…”
Section: ) Microtubule Filament Motility Over Stationary Kinesinmentioning
confidence: 99%
“…This finding is somewhat surprising given a previous report that the number of kinesins simultaneously bound to the microtubule is inversely tuned by transport velocity, 18 and given other reports that the force propelling each microtubule depends on the number of biomotors present. 29,30 We speculate that transport velocity influences the relative probability of maximal versus intermediate force production by a group of kinesin biomotors. We are working on future optical-trapping studies to examine this potential effect of transport velocity on force production by groups of biomotors.…”
Section: Transport Velocity Does Not Influence Spool Size At Steady Smentioning
confidence: 99%
“…On the other hand, the experimental trend of χ appears to qualitatively reproduce the trend seen in simulations (Figure 7(A),(B)). In future, the predictions of simulations could be tested in experiment, potentially using methods developed recently for micro patterning motors (49,50). Additionally, the relevance of such a transition from random to directed transport as a function of motor numbers, could also be tested by quantification of the number of motors involved in vivo in MT transport.…”
Section: Discussionmentioning
confidence: 99%